Współczesny rozwój lokalny i regionalny - Passella, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
World economy and its system are based on information economy and globalization proccess. Forces that fastening globalization are: information and telecommunication revolution, liberalization of economic relationships and development of importance of competition. Enterprises, cities, regions and countries try to reach as big as possible advanteges what leads to polarization of space. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 50-58